Implementasi Qanun Aceh Nomor 9 Tahun 2008 dalam Menyelesaikan Sengketa di Tingkat Gampong - Junaidi Junaidi; Muhaddis Muhaddis; Dicky Armanda; Taufik Gunawan (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
Custom and Customary Law are basically complementary laws, and are part of the national legal system, in relation to each other subject to laws and regulations and also subject to the provisions of Customary Law. The purpose of this study is to describe the effectiveness of Aceh Qanun Number 9 of 2008 in resolving disputes at the level of Ulee Blang Mane Village, Banda SaktiDistrict, Lhokseumawe City. This study uses a qualitative research method that is descriptive in nature by using techniques to obtain data through observation, interviews, and documentation. This study used 12 informants who were determined purposively consisting of Geuchik, Village Officials, Customary Figures and the parties to the case (household disputes, division of inheritance and disputes between neighbors) in Ulee Blang Mane Village, District, Lhokseumawe City. The results of the study explain that Aceh Qanun Number 9 of 2008 in resolving disputes at the Gampong Jawa Lhokseumawe level, Banda Sakti District, Lhokseumawe City has not been implemented properly.